VietNam's health present conditions and proposals of reorganization - Phan, Quang Dan (Boston, 1957)
The report contains much detail taken from the literature, and a great deal of constructive discussion of the current problems and the steps to be taken to deal with them. It is written from a nationalist point of view, with a sufficiently strong anti-French bias, but the author is well informed, and his principal concerns are the unification and welfare of the people.